The Role of Social Skills on Bullying Behavior Tendency with Friendship Quality as Mediator - Ardyta Kusumaningsih; Arum Febriani (Jurnal Psikologi, 2022)
Social skills have been known to predict bullying tendencies in adolescence. However, knowledge about the mechanisms by which social skills are linked to bullying tendency remains limited. The present study investigated whether friendship quality would mediate the link. A sample of 204 adolescents (16-18 years old; 163 girls; 41 boys) studying in Yogyakarta state high schools completed an online self-report of Bullying Tendency Scale, Social Skills Scale, and Friendship Quality Scale. Mediation analysis was conducted using PROCESS macro. Results showed that friendship quality could not mediate social skills with bullying tendency therefore hypothesis of this study was denied. However, by including gender, it was found that friendship quality has a significant role as a mediator for boys. Higher social skills were associated with higher friendship quality, and then higher friendship quality was associated with higher bullying tendency. It can be concluded that social skills are important for boys and girls to exercise positive interaction with peers and to have high friendship quality. However, it is more important for boys to have high friendship quality with positive peers.